Total hip arthroplasty, through the direct anterior approach, for a femoral neck fracture of ipsilateral transfemoral amputee: a case report - Zhao, Xiangde; Wang, Gangliang; Wang, Yukang; Chen, Jian (Frontiers in Surgery, 2025)
ObjectiveFemoral neck fractures in transfemoral amputees are rare, and their management remains controversial, particularly in individuals with short residual limb lengths. Traditional approaches to total hip arthroplasty (THA), such as the anterolateral, Hardinge, and posterior methods, present significant challenges, including difficulties in residual limb manipulation, femoral exposure, and postoperative swelling. The direct anterior approach (DAA), a minimally invasive technique, has not been previously reported for THA in this patient population. This case report aims to evaluate the feasibility and outcomes of the DAA for THA in a transfemoral amputee with a femoral neck fracture.MethodsWe present the case of a 64-year-old Han male with an ipsilateral transfemoral amputation who sustained a femoral neck fracture. The patient underwent THA using the direct anterior approach. The DAA was selected due to its minimally invasive nature and ability to navigate through the intermuscular interval, which facilitated improved manipulation of the residual limb and easier exposure of the femoral side. Standard surgical protocols were followed, and postoperative care included monitoring for complications such as infection, thrombosis, and dislocation.ResultsThe patient's postoperative recovery was uneventful, with no signs of infection, thrombosis, dislocation, or other complications. Notably, there was no significant residual limb swelling, which was attributed to the minimally invasive nature of the DAA. The patient achieved unrestricted hip mobility without postural restrictions and attained a Harris Hip Score of 84.78 at follow-up, indicating a favorable functional outcome.ConclusionsThis case demonstrates the efficacy and safety of the direct anterior approach for total hip arthroplasty in patients with high above-knee amputations. The DAA effectively addresses many challenges associated with traditional approaches, such as residual limb manipulation, femoral exposure, and postoperative swelling. These findings suggest that the DAA is a viable alternative for managing femoral neck fractures in transfemoral amputees, warranting further investigation in larger studies to validate its broader applicability.